2011
DOI: 10.1093/nar/gkr1146
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of DNA methyltransferase specificities using single-molecule, real-time DNA sequencing

Abstract: DNA methylation is the most common form of DNA modification in prokaryotic and eukaryotic genomes. We have applied the method of single-molecule, real-time (SMRT®) DNA sequencing that is capable of direct detection of modified bases at single-nucleotide resolution to characterize the specificity of several bacterial DNA methyltransferases (MTases). In addition to previously described SMRT sequencing of N6-methyladenine and 5-methylcytosine, we show that N4-methylcytosine also has a specific kinetic signature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
309
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 297 publications
(317 citation statements)
references
References 37 publications
5
309
1
2
Order By: Relevance
“…However, contrary to those studies, recent data from single-molecule, real-time (SMRT) DNA sequencing of bacterial genomes showed that many of the MTases tested exhibited high fidelity (218). Interestingly, that study also revealed that the E. coli Dam MTase is highly promiscuous (218).…”
Section: Future Perspectivesmentioning
confidence: 75%
See 1 more Smart Citation
“…However, contrary to those studies, recent data from single-molecule, real-time (SMRT) DNA sequencing of bacterial genomes showed that many of the MTases tested exhibited high fidelity (218). Interestingly, that study also revealed that the E. coli Dam MTase is highly promiscuous (218).…”
Section: Future Perspectivesmentioning
confidence: 75%
“…Interestingly, that study also revealed that the E. coli Dam MTase is highly promiscuous (218). Thus, those enzymes which have a broad specificity could have evolved to serve other roles in the cell, viz., the regulation of transcription and the modulation of DNA transaction processes.…”
Section: Future Perspectivesmentioning
confidence: 94%
“…In an effort to identify all three oxi-mC species simultaneously in the C. cinerea DNA, we turned to SMRT sequencing (29)(30)(31). 5mC and 5hmC are only weakly detected by SMRT sequencing (15), whereas 5caC yields a strong signal (16).…”
Section: Resultsmentioning
confidence: 99%
“…SMRTbell template libraries were prepared as previously described (53,54). SMRT sequencing was carried out on the PacBio RSII instrument using standard protocols for large insert SMRTbell libraries.…”
Section: Methodsmentioning
confidence: 99%